2013
DOI: 10.1371/journal.pone.0081452
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Small Noncoding RNAs during the Transition from Dormant Embryo to Germinated Embryo in Larches (Larix leptolepis)

Abstract: Small RNAs (sRNAs), as a key component of molecular biology, play essential roles in plant development, hormone signaling, and stress response. However, little is known about the relationships among sRNAs, hormone signaling, and dormancy regulation in gymnosperm embryos. To investigate the roles of sRNAs in embryo dormancy maintenance and release in Larix leptolepis, we deciphered the endogenous “sRNAome” in dormant and germinated embryos. High-throughput sequencing of sRNA libraries showed that dormant embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Therefore, the potential absence of heterochromatic siRNAs in conifers Morin et al, 2008) and lycophytes (Banks et al, 2011) could reflect secondary loss of the pathway in those specific lineages. However, more recent data show that, for conifers, endogenous 24-nucleotide siRNAs can be found, albeit sometimes in tissue-specific patterns (Nystedt et al, 2013;J. Zhang et al, 2013) or in unique lineages such as cycads and Gingko (Chávez Montes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the potential absence of heterochromatic siRNAs in conifers Morin et al, 2008) and lycophytes (Banks et al, 2011) could reflect secondary loss of the pathway in those specific lineages. However, more recent data show that, for conifers, endogenous 24-nucleotide siRNAs can be found, albeit sometimes in tissue-specific patterns (Nystedt et al, 2013;J. Zhang et al, 2013) or in unique lineages such as cycads and Gingko (Chávez Montes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several hints suggesting that the heterochromatic siRNA pathway may indeed be present outside of angiosperms. Significant amounts of 24-nucleotide RNAs have been observed in conifers in a highly tissue-specific manner (Nystedt et al, 2013;J. Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reverse genetic analyses of these homologs, coupled with sRNA-seq analyses of the mutants, has shown that hc-siRNAs exist in the moss P. patens (Cho et al, 2008;Coruh et al, 2015), which implies that the pathway was most likely present in the last common ancestor of all land plants. Whether hc-siRNAs have been specifically lost in the conifers and/or ferns remains an open question, but the presence of high levels of 24 nt RNAs in specific tissues of the conifers Norway spruce (Picea abies) (Nystedt et al, 2013) and Japanese larch (Larix leptolepis) (Zhang et al, 2013) suggests that this may not be the case. Thus, as a class of endogenous plant small RNA, it is now clear that hc-siRNAs are probably as universally conserved in land plants as the miRNA and phasiRNA classes.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%
“…Reports on sRNA studies in gymnosperm seeds have been lacking so far, but previous work on conifer sRNAs have reached different and contradicting conclusions regarding the presence of 24-nt sRNAs, typically associated with hetsiRNAs, in the sRNA transcriptome of the conifers clade Morin et al 2008;Lee et al 2011;Chávez-Montes et al 2014;Wan et al 2012;Zhang et al 2012bZhang et al , 2013bNystedt et al 2013;Niu et al 2015). In somatic embryo-derived material from the conifer Japanese larch (Larix leptolepis) the presence of significant amounts of 24-nt sRNAs has been reported (Zhang et al 2012b(Zhang et al , 2013b, but it would be interesting to check for the presence of these sRNAs in conifer seeds.…”
Section: Abundance Of Small Rnas In Seed Tissuesmentioning
confidence: 99%
“…In somatic embryo-derived material from the conifer Japanese larch (Larix leptolepis) the presence of significant amounts of 24-nt sRNAs has been reported (Zhang et al 2012b(Zhang et al , 2013b, but it would be interesting to check for the presence of these sRNAs in conifer seeds.…”
Section: Abundance Of Small Rnas In Seed Tissuesmentioning
confidence: 99%